EVALUATION AND SELECTION OF ALFALFA MUTANT RESULTS OF GAMMA RAY IRRADIATION ON ABIOTIC STRESS - D.N., HARIANJA; KARTI, P.D.M.H.; PRIHANTORO, I. (Majalah Ilmiah Peternakan, 2022)
Alfalfa is a leguminous protein source with high nutritional value and economic value. Abiotic stress inhibits growth and reduces alfalfa production in many aquaculture systems. New varieties were developed by gamma-ray mutation induction. The selection was carried out to obtain superior abiotic stress-tolerant plants. This study aims to evaluate and select alfalfa mutants under abiotic stress conditions. The design used in this study was a comple- tely randomized design (CRD) with a factorial pattern. The first factor is the type of acid-tolerant mutants, namely A44, A54, A35, and A45. The second factor is the PEG level which is 10%, 15%, and 20%. The variables observed included viability, plant height, number of leaves, leaf wilting, leaf color, media shrinkage, and wet weight. Alfalfa mutants resulting from acid-tolerant gamma irradiation were evaluated under dry stress conditions. The results showed that mutation induction resulted in various responses to growth. Gamma-ray irradiation produces plants that are tolerant to abiotic stress conditions. From the selection results obtained superior mutant candidates that are tolerant of acid stress and dry conditions. The A44 mutant had better tolerance to dry stress than others and became an acid- and dry-tolerant alfalfa mutant.